Multidiscip Cancer Investig 2019
DOI: 10.30699/acadpub.mci.3.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and Apoptotic Effects of Ectoine and Hydroxyectoine on Non-Small Cell Lung Cancer cells: An in-vitro Investigation

Abstract: Introduction: Streptomyces manage the osmotic stress by collecting compatible solutes or osmolytes. Ectoine, 1,4,5,6-tetrahydro-2-methyl-4-pyrimidine carboxylic acid, and 5-hydroxyectoine are among the most common osmolytes of this bacteria and have an active role in protecting the genetic material of this microorganism as well as providing resistance to environmental pressures. In this research, the antiproliferative and apoptotic effects of ectoine and 5hydroxyectoine on human non-small cell lung cancer (NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…On the other hand, seven out of nine BGCs of Aa3_DN213_3F7 gave hits to the MIBiG repository ( Table S4 ). Similarly, four BGCs were related to clusters involved in the production of substances with reported anticancer activity: carotenoids (MIBiG:BGC0000636) (85% similarity) [ 54 , 55 ], ectoines (MIBiG:BGC0000853) (75% similarity) [ 56 ] and the siderophore desferrioxamine E (MIBiG:BGC0001478) (50% similarity) [ 57 ] ( Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, seven out of nine BGCs of Aa3_DN213_3F7 gave hits to the MIBiG repository ( Table S4 ). Similarly, four BGCs were related to clusters involved in the production of substances with reported anticancer activity: carotenoids (MIBiG:BGC0000636) (85% similarity) [ 54 , 55 ], ectoines (MIBiG:BGC0000853) (75% similarity) [ 56 ] and the siderophore desferrioxamine E (MIBiG:BGC0001478) (50% similarity) [ 57 ] ( Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…β-carotene is a successful carotenoid in the global market with many industrial applications, including prevention of cancer [ 55 ]. In the case of ectoines, Sheikhpour et al [ 56 ] showed that ectoine and hydroxyectoine isolated from Streptomyces induced apoptosis in lung cancer cells. Another compound involved in the cytotoxicity of Aa3_DN213_3F7 could be related to desferrioxamine E, a synonym for nocardamine.…”
Section: Discussionmentioning
confidence: 99%
“…This cluster comprises regulatory genes, core, and additional genes involved in the biosynthesis of prodigiosin derivatives, similar to that of red gene cluster of S. coelicolor A3(2). Cluster 19 displayed 100% similarity with ectoine biosynthesizing genes, indicating that BSE6.1 is capable of producing ectoine-an anticancer molecule [89] that regulates osmotic stress [90] and acts as a stress protectant against various environmental stresses [91]. Clusters 7 and 17 displayed siderophore genes that were involved in the production of enduracidin and desferrioxamine B, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Ectoine is commonly expressed by bacteria to survive in harsh environments, protecting these microorganisms against extreme osmotic stress [34][35][36][37][38] . As a compatible solute, ectoine has been shown to be safe as it does not interfere with the host's metabolism while offering some beneficial effects including antioxidant and protection against ionizing radiation [39][40][41][42] . Apart from that, a recent study by Sheikhpour et al (2019) showed that ectoine induced apoptosis in lung cancer cells without affecting normal cells.…”
Section: Data Descriptionmentioning
confidence: 99%